The Istanbul declaration for global health (Italian Journal of Public Health, 2010)
More than 2,300 public health professionals from around the world attended the 12th World Public Health Congress, in Istanbul, between April 27th and May 1st, 2009. Participants from 120 countries from all corners of the globe advocated for different disciplines and composed an eclectic and propitious audience for a profound discussion on the part each individual – as well as national associations, at the country level, and the Federation, at the global level – plays in facing the challenges currently posed to the field of Public Health.